Revitalisasi Cerita Rakyat dan Tradisi Sasak melalui Teater Komunitas: Studi Kasus Kampoeng Baca Pelangi - Waluyan, Roby Mandalika; Mawardi, Taufik; Nahdlatuzzainiyah, Nahdlatuzzainiyah; Hardi, Rahmat Sulhan; Renda, Rapi (Universitas Muhammadiyah Mataram, 2026)
This study analyzes the role of Kampoeng Baca Pelangi (KBP) in Merce Timur Hamlet, Selat Village, Narmada District, West Lombok as a community literacy platform that develops theatrical performance arts based on Sasak folklore and traditions. As a non-formal learning space that began as a community literacy movement, KBP has developed into a creative center that facilitates children and youth to learn, adapt, and re-perform local stories such as the legends of Princess Cilinaya, Princess Mandalika, Peraq Api, and various other Lombok cultural narratives. This study uses a qualitative approach with a case study design, through in-depth interviews, observations of the rehearsal and performance process, and a review of community documentation and local media publications. The results show that KBP plays a role in: (1) strengthening the cultural identity of the younger generation through the integration of literacy with traditional theater practices; (2) creating a collaborative space between communities, educators, and higher education institutions; and (3) presenting a community-based cultural revitalization model that is adaptive to local needs. The findings also indicate major challenges in the form of limited resources, regeneration, and minimal sustainable promotional support. Overall, this study confirms that the synergy between literacy, education, and performing arts is an effective strategy in revitalizing Sasak culture at the community level, while also providing a basis for developing policies and programs to strengthen local culture in West Lombok.